Hubungan Penerangan Dan Housekeeping Terhadap Kecelakaan Kerja Pada Pekerja Konstruksi Bangunan Pt. Dap Di Perumahan Citra Land Bagya City Medan Tahun 2019 - Marlinang Silalahi (Jurnal Mutiara Kesehatan Masyarakat, 2019)
A work accident is any unsaved action or condition that may result in a loss. A work accident is an adverse occurrence or event that is detrimental to humans, damaging property or loss to the process.Social Security Administering Agency (BPJS) in North Sumatera, said in the area of Medan Belawan There are 1,094 cases, Tanjung Morawa There are 1,218 cases and Medan city as many as 484 cases, with an average of 15 cases of occupational accidents every day.The type of research used in this study is observational research with cross-sectional methods. The population of this research is building workers in the construction of Citra Land Bagya City Medan, as many as 30 respondents.The samples in this study were all construction workers housing the Citra Land Bagya City Medan.The sampling technique in this study is a total sampling of 30 respondents. The results of this study were tested statistically by using Chi Square test with a confidence level of 95%. The results showed that there was a housekeeping relationship to the occurrence of a work accident with p value of 0,048 < 0.05. Then there is no lighting relationship with the occurrence of work accident with p value 0,398 > 0.05. It is recommended for building workers to discipline using the PPE when working, and supervisors pay more attention to housekeeping in the construction work area.